The Influence of Classical Counseling, BMB3 Strategy, Education In Understanding of Addiction, Development of Structured Positive Behavior on The Dangers of Behavioral Addiction and Napsa - Famahato Lase (Edumaspul: Jurnal Pendidikan, 2022)
Classical counseling services need to be provided to every student, to prevent them from the dangers of behavioral and napsa. The purpose of this study was to reveal the effect of classical counseling, BMB3 strategies, education on understanding the dangers of addiction, fostering structured positive behavior, on the prevention of the dangers of behavioral and napsa, using quantitative research methods. The study population was all students of SMP Bunga Mawar Gunungsitoli, and the sample was drawn by purposive sampling, namely six study groups of class VII students of 210 people. The research instrument used to collect data was a closed questionnaire, which was circulated to a number of respondents as a data source. Data were analyzed using inferential statistics, multiple linear regression analysis, to answer research questions according to the proposed hypothesis. The results of the study concluded that classical counseling services, BMB3 strategies, education on understanding the dangers of addiction, fostering structured positive behavior, jointly and partially provide a very large influence and contribution to preventing the dangers of behavioral and napsa. If there is an increase in the provision of classical counseling services, the application of the BMB3 strategy in services, education on understanding the dangers of addiction, and fostering positive behavior, the prevention of the dangers of behavioral and napsa will also increase.